(untitled) (Itinera, 2019)
This essay explores the theoretical and material possibilities of a “language of space” in theatre as found in the works of Antonin Artaud and James Turrell. By drawing a bridge between Artaud’s philosophy of theatre and Turrell’s approach to conceptual art, we consider how the art of “stage work” is intimately linked to the fundamental philosophical questions of language and being. The foundations of our inquiry rest on the phenomenological analyses of French philosopher Georges Didi-Huberman. The main elements of our reflection concern the notions of the poetics of language and the substantiality of space.